Is Chinese Spring Festival a key point for glycemic control of patients with type 2 diabetes mellitus in China? - Huilin Xu; Li Cao; Li Cao; Li Cao; Jun Li; Fen Zhang; Weijie Wang; Tongtong Liang; Xiaohua Liu; Chaowei Fu; Chaowei Fu; Chaowei Fu (Frontiers Media S.A., 2022)
ObjectivesThis study aims to explore the long-term trend of fasting blood glucose (FBG) among urban patients with type 2 diabetes mellitus (T2DM) and the impacts of the Chinese Spring Festival on their glycemic control in urban China.MethodsThe general information and longitudinal monitoring data of patients with T2DM in Minhang District, Shanghai China from 15 December 2006 to 31 December 2015 were collected. The FBG records were grouped into three periods, namely, the preholiday period (2 months right before the Chinese Spring Festival), the holiday period (from 28 December to 7 January of the lunar calendar year), and the postholiday period (2 months after the Chinese Spring Festival). The Mann-Kendall trend test and Cochran-Armitage trend test were occupied to explore the long-term trend, and paired t-test and chi-square (χ2) test were used to determine the differences in glycemic level and control rate between the preholiday and postholiday periods, respectively.ResultsFrom 2007 to 2015, the glycemic control rate in patients with T2DM showed an upward trend (P < 0.001), and the FBG level showed a decreasing trend (P = 0.048). After the Chinese Spring Festival, the glycemic control rate decreased significantly (P < 0.001), and the FBG level increased significantly (P < 0.001) compared to those during the preholiday period. The incidence of hypoglycemia increased during holidays. Patients who were aged 60-69 years, overweight or obese, with hypertension, with a disease duration of <3 years, or with poor glycemic control in one previous year were more likely to be affected by the holiday.ConclusionChinese Spring Festival is a key point for glycemic control of patients with T2DM in China. Intensive holiday-specific diabetic healthcare needs to be further improved, and community-based interventions should be developed and implemented to control the possible holiday effects.